2019
DOI: 10.3390/ijerph16224325
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Korean Medicine-Based Forest Therapy Programs Providing Electrophysiological Benefits for Elderly Individuals

Abstract: We aimed to develop forest therapy programs (FTPs) to prevent dementia and related health problems in the elderly population, with the assumption that health benefits are FTP-type specific and depend on the participant’s psychophysiological traits. For this purpose, we developed two distinct FTPs, namely, a guided-breathing meditation program (BP) and a walking program (WP); we adopted the approach of Sasang constitutional (SC) medicine, which categorizes individuals into one of three SC types (SC1, SC2, or SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 71 publications
(85 reference statements)
2
19
0
Order By: Relevance
“…In 2019, HRV was suggested as a useful marker for disease prevention in the elderly (Tan et al, 2019). The authors of this study have also shown that the HRV indices, which were measured with the same instruments and protocols as those in this study, significantly increased after therapy in forest, resulting in a positive effect (Yi et al, 2019).…”
Section: Introductionsupporting
confidence: 57%
“…In 2019, HRV was suggested as a useful marker for disease prevention in the elderly (Tan et al, 2019). The authors of this study have also shown that the HRV indices, which were measured with the same instruments and protocols as those in this study, significantly increased after therapy in forest, resulting in a positive effect (Yi et al, 2019).…”
Section: Introductionsupporting
confidence: 57%
“…Recently, thanks to the development of IT technology, a convenient and high quality low-channel wireless EEG measurement system has been widely used [34,35]. The authors of this study have shown that two-channels EEG systems, measured at prefrontal region, show reliable data quality and significant clinical results [36][37][38]. With two-channels EEG system, the authors have also shown that MDF and ATR are correlated negatively with the MMSE scores of elderly people (total = 496, males = 163, females = 331) [36] Correlations between EEG changes and neuroimaging findings have been reported in many studies as well.…”
Section: Introductionmentioning
confidence: 84%
“…Some forest therapies conducted for the elderly population are based on or run in combination with walking, physical exercise, cognitive intervention, and social activity [ 24 , 25 , 26 ]. The reported benefits include effects on blood pressure, arterial stiffness, pulmonary function, salivary cortisol level, quality of life, depression and anxiety, mood state, and blood biomarkers related to cardiovascular disease [ 6 , 25 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%